2019
DOI: 10.16910/jemr.12.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the disparity vergence fusion sustain component

Abstract: The stereotypical vergence response to a step stimulus consists of two dynamic components: a high velocity fusion initiating component followed by a slower component that may mediate sustained fusion.  The initial component has been well-studied and is thought to be controlled by an open-loop mechanism. Less is known about the slow, or fusion sustaining component except that it must be feedback controlled to achieve the positional precision of sustained fusion.  Given the delays in disparity vergence control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similar to PD subjects, the controls were tested at both 55 cm and 30 cm. Convergence was measured using LED targets at 20, 55, 150, and 244 cm distances along the sagittal plane where the subjects were asked to shift their gaze from the distantly located target to near (Searle and Rowe, 2016;Kang et al, 2018;Semmlow et al, 2019Semmlow et al, , 2021.…”
Section: Study Participants and Experiments Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to PD subjects, the controls were tested at both 55 cm and 30 cm. Convergence was measured using LED targets at 20, 55, 150, and 244 cm distances along the sagittal plane where the subjects were asked to shift their gaze from the distantly located target to near (Searle and Rowe, 2016;Kang et al, 2018;Semmlow et al, 2019Semmlow et al, , 2021.…”
Section: Study Participants and Experiments Protocolmentioning
confidence: 99%
“…There are two key sensory drives for inducing vergence while looking at targets at different depths, which are (1) visual blur under monocular viewing that induces accommodative vergence; and (2) retinal disparity under binocular viewing, i.e., differences in the spatial position of the image on two retinas that induces disparity-driven vergence. There are two key motor components of disparity-driven vergence, which are (1) the fusion initiation component, i.e., the open loop or pulse of neural activity facilitating the initial movement responsible for vergence, and (2) the fusion maintenance component driven by visual or internal feedback to align the eyes accurately to maintain a fusion of the binocular image of the target (Semmlow et al, 2019(Semmlow et al, , 2021. A handful of studies have quantified vergence in PD and have reported increased latency with variable effects on convergence velocity and gain (Hanuška et al, 2015;Gupta et al, 2021a,b).…”
Section: Introductionmentioning
confidence: 99%